In-situ observation of MH formation/decomposition in unconsolidated sands recovered from the South China Sea. (February 2019) - Sun, Ronghui; Fan, Zhen; Yang, Mingjun; Zhao, Jiafei; Song, Yongchen
Abstract: Methane hydrates (MH) have been viewed as an important potential energy resource. Assessments about the MH formation and dissociation behavior in porous deposits which are consistent to in-situ reservoir conditions are essential for the safe and efficient production of natural gas hydrates in submarine sediments. In this study, the formation and decomposition behavior of MH in unconsolidated sands recovered from the South China Sea were investigated by the charge-coupled-device (CCD) camera visualization. Deformation of the sediment was observed during both MH formation and decomposition processes. The experimental results indicated that the interactions between MH and the host porous materials during the phase-transition processes could play an important role for the deformation of the sediment. Thus, further studies are needed.